Patient Perception of Medical Learners and Medical Education during Clinical Consultation at a Family Medicine Residency - Goerl, Kyle; Ofei-Dodoo, Samuel (Kansas Journal of Medicine, 2018)
Introduction. Experience in treating patients under supervision of faculty is an important factor in medical education at all levels. However, unpleasant patient experiences with a medical learner during clinical consultation can damage the relationship between the medical learner, physician supervisor, and patient. A goal of this study was to examine patient experiences and preferences regarding medical learners during clinical consultation at a family medicine residency clinic. Another goal was to determine factors relating to patients’ experiences and preferences regarding medical learners. Methods. This cross-sectional study relied on patients completing a survey designed from extant questionnaires to measure patients’ experiences and preferences relating to interactions with medical learners at a family medicine clinic. Data were collected from 216 patients between December 2016 and August 2017. We correlated patients’ feelings, overall experiences with medical learners and the importance of medical education. Results. There was a 93% participation rate. The patients rated their overall experiences with medical learners as 3.8 on a 5-point scale, suggesting positive experiences. Eighty-eight percent prefer not more than three medical learners to be involved in their care during clinical consultation. Patients’ overall experiences with medical learners participating in medical care correlated with their preferences regarding medical learners’ involvement in their treatment (r[209] = .524; p = 0.01). Patients’ perception of medical learners participating in medical care correlated with the importance of medical education (r[209] = .878; p = 0.01). Conclusions. The results showed that most patients have positive experiences with medical learners and are generally in favor of medical education. Kans J Med 2018;11(4):102-105.